Career and Retirement Counselling in Oyo Metropolis, Oyo State Nigeria - Yekinni, Lukuman Oyewole; Bakare, Abiodun Oluwatobi (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
Career and retirement counselling is crucial due to the evolving global workforce and demographics, which significantly impact an individual's well-being and societal dynamics. The study explores career and retirement counselling in Oyo Metropolis, Nigeria, using a survey. 400 participants (ages ranging from 25–70) were selected randomly in Oyo metropolitan area from counselling centres, workplaces, and retirement communities using a valid and reliable instrument. Data were collected on various dimensions of career counseling effectiveness, including increased self-efficacy, enhanced career clarity, improved decision-making skills, satisfaction with career choices, exploration and adaptability, and long-term career development. The findings reveal a varying perspective on the perceived effectiveness of career counseling, with respondents expressing agreement on certain aspects while disagreeing on others. Specifically, respondents agreed that career counseling positively influences decision-making skills, satisfaction with career choices, exploration, and long-term career development. However, respondents disagreed with its effectiveness in enhancing self-efficacy, confidence, and career clarity. The study also established that there is a significant difference in the role of retirement counselling facilitating a successful transition from active work life to retirement based on counselling status. These results accentuate the need for tailored interventions that address specific areas of improvement within career counseling services. Therefore, it recommends, among others, that career counselling should be incorporated into daily life to enhance individuals' career development and decision-making and that counsellors should emphasise the importance of career counselling before retirement, which is crucial for a successful transition from active work-life to retirement and addresses psychological and emotional challenges.